The Role of Big Data and Artificial Intelligence Intelligence in Strategic Business Decision Making in the Global era a Literature Review - Sumarno Manrejo; Markonah Markonah; Johan Hendri Prasetyo; Yohanes Ferry Cahaya; Herni Pujiati (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2026)
Study This aim For analyze contribution Big Data and Artificial Intelligence (AI) strategic in the decision-making process decision company , as well as How innovation technology This capable increase effectiveness , accuracy time and precision in determine policy business in the contemporary digital era . Research This done with Systematic Literature Review approach with review 14 works scientific published in range 2023-2025 period . Data source obtained through academic platforms leading including Google Scholar and Semantic Scholar , with specification research that explores correlation between Big Data technology , AI, and business decision -making processes. Findings studies disclose that implementation of Big Data in significant transforming the decision-making process decision through capability real-time analytics , detection market patterns , and optimization performance operational . Meanwhile that , AI plays a role as complementary with his abilities do massive data processing , prediction business , and providing strategic insights . Synergy second technology This capable building a superior value proposition in environment global business . Scope study This limited to analysis document secondary so that need study advanced based approach empirical For strengthen validity findings in various context industry .